2013
DOI: 10.1021/nn400466t
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Drape Minimizes the Pinning and Hysteresis of Water Drops on Nanotextured Rough Surfaces

Abstract: Previous studies of the interaction of water with graphene-coated surfaces have been limited to flat (smooth) surfaces. Here we created a rough surface by nanopatterning and then draped the surface with a single-layer graphene sheet. We found that the ultrasheer graphene drape prevents the penetration of water into the textured surface thereby drastically reducing the contact angle hysteresis (which is a measure of frictional energy dissipation) and preventing the liquid contact line from getting pinned to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 31 publications
3
46
1
Order By: Relevance
“…The CA of water droplets on both bare Ni mesh and GCNM are nearly identical, as shown in Supplementary Fig. 5, demonstrating the wetting transparency2122232425 of the graphene coating on the metal substrates. To evaluate the protective effect of graphene against thermal oxidation, we thermally annealed both GCNM and bare Ni mesh at 400 °C for 4 h. After the thermal annealing process, the colour of the bare Ni mesh significantly changed from silver to dark blue, whereas the colour of the graphene-coated samples remained unchanged.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The CA of water droplets on both bare Ni mesh and GCNM are nearly identical, as shown in Supplementary Fig. 5, demonstrating the wetting transparency2122232425 of the graphene coating on the metal substrates. To evaluate the protective effect of graphene against thermal oxidation, we thermally annealed both GCNM and bare Ni mesh at 400 °C for 4 h. After the thermal annealing process, the colour of the bare Ni mesh significantly changed from silver to dark blue, whereas the colour of the graphene-coated samples remained unchanged.…”
Section: Resultsmentioning
confidence: 64%
“…In fact, the wetting transparency effect can also be extended to strongly hydrophobic (that is, rough) substrates24, if the graphene coating is deposited in-situ via chemical vapour deposition (CVD) and conforms to the surface roughness features of the substrate. These results indicate that graphene-coated metal substrates can be used as water harvesting devices with greatly improved anti-oxidation and anti-corrosion capabilities, without disrupting the intrinsic wettability of the underlying substrate2122232425. However, previous studies only investigated the passive wettability of graphene and graphene hybrid composites; to the best of our knowledge, active control of the wettability of graphene-coated surfaces has not been investigated thus far.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…5b), the bigger one is advancing angle  A and the smaller one is receding angle  R , again, the difference between them can be seen as contact angle hysteresis. A few of theoretical analyses and experiments [6,[12][13][14][15][16][17][18] show that droplets in Cassie state can provide smaller contact angle hysteresis as well as larger contact angle. Hence for many industrial applications, such as self-cleaning surfaces, people show more interests in this droplet state.…”
Section: Introductionmentioning
confidence: 99%
“…Hence for many industrial applications, such as self-cleaning surfaces, people show more interests in this droplet state. Eklavya et al [16] draped the nanotextured surface with a single-layer graphene sheet to avoid the water intruding into the textured surfaces and in the meantime hold the droplet in an ideal Cassie state. Their experiments showed that the droplet separated by the graphene sheet could hardly be pinned to the substrate and the contact angle hysteresis was reduced significantly.…”
Section: Introductionmentioning
confidence: 99%